2009
DOI: 10.1123/ijsnem.19.5.547
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Effects of Glycerol-Containing Hyperhydration Solutions on Gastric Emptying and Intestinal Absorption in Humans and in Rats

Abstract: Glycerol-induced hyperhydration (GIH) has been shown to improve fluid retention and endurance performance compared with water-induced hyperhydration. The goal of this article is to report on what is known and unknown about how glycerolcontaining hyperhydration solutions (GCHSs) are processed at the stomach and intestine level, propose strategies to improve the efficacy of GIH, and provide research questions for future studies. Through statistical analyses, it is demonstrated that the effectiveness of GCHSs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…When compared with water ingestion alone however, fluid retention is increased (~8 ml.kg -1 body mass) when osmotically active agents such as sodium or glycerol are consumed with the fluid [13]. Furthermore, the addition of glucose to a solution containing glycerol may further enhance fluid absorption and be of further benefit from a metabolic perspective [17]. A recent meta-analysis concluded that the use of glycerol hyperhydration in hot conditions provides a small (3% power output, Effect Size=0.35) but worthwhile enhancement to prolonged exercise performance above hyperhydration with water [13].…”
Section: Introductionmentioning
confidence: 99%
“…When compared with water ingestion alone however, fluid retention is increased (~8 ml.kg -1 body mass) when osmotically active agents such as sodium or glycerol are consumed with the fluid [13]. Furthermore, the addition of glucose to a solution containing glycerol may further enhance fluid absorption and be of further benefit from a metabolic perspective [17]. A recent meta-analysis concluded that the use of glycerol hyperhydration in hot conditions provides a small (3% power output, Effect Size=0.35) but worthwhile enhancement to prolonged exercise performance above hyperhydration with water [13].…”
Section: Introductionmentioning
confidence: 99%
“…numerous studies, reviewed by Goulet (2009), in humans and rats, showing that solutions containing glycerol maintain fluid retention. Furthermore, combining glycerol with glucose in a 2:1 ratio is reported to improve the rate of water and electrolyte absorption in rats (Allen et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…The percent increase in the (PeA/L) of ketotifen fumarate in jejunum and ascending colon after addition of 15% ethanol was almost 100% in both segments respectively. Glycerol had increased the The major reason for this increase of the absorptive clearance upon addition of ethanol, glycerol, and propylene may be due to membrane fluidization effect of these cosolvents and disruption of the lipid bilayer structure which enhances transcellular absorption of ketotifen fumarate [26][27][28][29] .Sinceour results had shown that ketotifen fumarate is dependent mainly on the transcellular diffusive pathway in its transport across the intestinal membrane ( Table 3) so that these cosolvents had a highly significant effect on the transcellular absorption of this compound in both ISSN: 2357-0547 (Print)…”
Section: Effect Of Cosolvents On Membrane Transport Parameters Of Ketmentioning
confidence: 99%
“…So that it easily partitioned into the phospholipid structure of the cell membrane resulting in an increase in the transcellular diffusive absorption. Furthermore, both ethanol and glycerol are potent inhibitors to pglycoprotein [25][26][27][28] . This inhibits the back efflux of the drug to the intestinal lumen with subsequent increase in absorptive clearance of ketotifen fumarate.…”
Section: Research Article / Japr Issn: 2357-0539 (Online)mentioning
confidence: 99%